Headache: Safaty of Acetaminiphen during pregnancy. Systematic review - Takahashi-Ferrer, Carolina Mayo (2022)
Introduction: One of the most recurrent symptoms during pregnancy is headache, to relieve it the most prescribed drug is the analgesic Acetaminophen (paracetamol). Objectives: To describe the safety of the use of acetaminophen in case of headache during pregnancy. Material and methods: It is a systematic review of research works, where the PRISMA recommendation was followed by searching for scientific articles published in: Science Direct, Elsevier, Ebsco, Pubmed, Redalyc, Scielo, Google academic, Latindex, Lilacs and Alicia, during the period 2018 to 2022. Results: From an initial of 447742 studies corresponding to the bibliographic search, without applying filters, the PRISMA format was used according to its recommendation, leaving a total of six scientific articles, of which five articles recommend the use of acetaminophen (paracetamol) in case of headache in pregnant women, they also state that its use is safe throughout pregnancy, in particular Chaves E, et al., (2020) points out that according to the risk classification of the Food Administration and Drug Administration (FDA), acetaminophen is classified as Category B, which means that this drug has not been described as having any risk to the fetus. Conclusions: The use of acetaminophen during pregnancy in case of headache is safe.